Insights from b value analysis of Campi Flegrei unrests - Vincenzo Convertito; Cataldo Godano; Giuseppe Petrillo; Anna Tramelli (Scientific Reports)
Abstract The Campi Flegrei caldera has experienced several episodes of volcanic unrest during the last few centuries, most notably in 1982–1984 and 2005–present. These periods of unrest are characterized by ground uplift, seismic swarms, and increased degassing. In this study, we compare the seismicity and associated b value variations during the 1982–1984 and 2005–2024 unrest periods. The b value is calculated using the novel b more positive method, which improves upon traditional approaches by analyzing the magnitude difference between successive earthquakes, without the need to estimate the completeness magnitude. Our results show significant differences in the spatial and temporal evolution of b values between the two unrest periods. In particular, the 2005–2024 unrest exhibits a slower ground uplift rate but higher fluctuations in the b value, especially in shallower seismicity, possibly suggesting different underlying mechanisms compared to the 1982–1984 crisis. We also observe distinct regions of increased stress, particularly beneath Pozzuoli harbor and Pisciarelli area for deeper seismicity, during the ongoing unrest. Our findings provide valuable insights into the evolution of Campi Flegrei volcanic systems and highlight the importance of continuous monitoring of the b value as a potential strain meter for describing volcanic activity.